The Introduction of Alphabet Letters in Basic English Through "Lokuter" - Laily Mardiyati (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
In the realm of cognitive development of early childhood 4-5 years or group A there are indicators of the level of development achievement pairing or connecting letters of the alphabet both the components of vowels and consonants in English. The English alphabet for early childhood is something that is newly known, or just seen and heard so that the need to recognize letters of the alphabet in an interesting and fun way.To help introduce and understand the letters of the alphabet and be arranged into words in English in Group A RA Perwanida Wonosobo, located on Jalan Tumenggung Jogonegoro No. 37 Our Wonosobo uses a game technique called the "Flying Horse Jump" GameThe game technique "Flying Horse Jump" uses a simple tool made from used banners as the base of the game that is drawn according to the desired pattern and given the letters of the alphabet along with how to pronounce each pattern. The purpose of making this article is to provide references and input to teachers, guardians of students and the wider community so that the presentation of subject matter, especially basic English introduction material for kindergarten students is packaged creatively, innovatively and on target. The benefits are that it can be used as a teacher's reference to stimulate student enthusiasm and motivation in learning, and can be used as an alternative for parents of students to make appropriate, practical and logical ways in providing understanding to students relating to the introduction of the letters of the alphabet in basic English during this pandemic.